Possibilities of gastroprotective therapy in NSA1Dinduced gastropathies with De-Nol - A. E. Karateev; E L Nassonov; S G Radenska-Lopovok (Научно-практическая ревматология)
Objective. To assess efficacy of De-Nol in NSAID-induced gastropathies. Material and Methods. 45 pts with rheumatic diseases taking NSAID with gastric and/or duodenal ulcer up to 1 cm of size or multiple (>10) gastric erosions (MGE) confirmed with endoscopy were included. They were randomized to receive De-Nol 240 mg twice a day with amoxicillin 2 g/day and furosolidon 400 mg/day (subgroup la) or De-Nol 240 mg twice a day as monotherapy (subgroup lb). Group 2 patients were treated with ranitidin 150 mg twice a day. Demographic parameters, nosological structure, treatment of the main disease and gastrointestinal changes stmcture in these groups did not significantly differ. Elderly women with rheumatoid arthritis and gastric ulcer were prevalent. HP was revealed in 73,3% and 90% of pts. Dyspepsia and heartburn were present in 90% and 93,3% respectively. Therapy efficacy was assessed after 4 weeks. Preventive effect was assessed in 2 months after the successful treatment course. Preventive doses of the drugs were equivalent to ? of treatment doses. Results. 3 pts from group 1 and 1 pt from group 2 were lost to follow up. I pt from group I stopped De-Nol prematurely because of adverse event (diarrhea). Ulcer and erosion healing was achieved in 22 from 26 pts of group I (86.6%) and from 7 from 14 pts of group 2 (50%), p=0.036. After the course of therapy remained in in 4 pts of group 1 (15,4%) and 9 pts of group 2 (64,3%), p=0.003. 3 pts receiving De-Nol had adverse events (2 - diarrhea, 1 - wind). Antihelicobacter effect was assessed in 7 pts of subgroup la. Eradication was achieved only in 3. Antiulcer effect in subgroup la and lb did not differ (88,8% and 82,4% respectively, p=0,732. HP was present in 12 from 20 pts (60%) of subgroup lb. Antiulcer therapy was effective in 6 from 7 of HP-negative (85,7%) and in 8 from 10 of HP positive (80%) pts, p=0,S4l. Preventive effect was assessed in 15 pts of group I and 5 pts of group 2. Relapse frequency was 13,3% and 20% respectively. Conclusion. De-Nol is effective in NSAID-induced gastropathies and its effect does not depend on HP.